Pengaruh Problem Based Learning Terhadap Keterampilan Kolaborasi Dan Berpikir Tingkat Tinggi - Fatynia Ilmiyatni; Tri Jalmo; Berti Yolida (Universitas Lampung, 2019)
This study aims to determine the effect of PBL on student collaboration and high-order thinking (HOT) skills. This study was a quasi-experimental with non-equivalent pretest-posttest design. The sample of this study were students of Senior High School 3 Bandar Lampung X MIA 2 (experimental group) and X MIA 3 (control group) taken used purposive sampling technique. The collaboration skill data obtained from the collaboration skill observation sheet descriptically analysed. The HOTS data were in the form of pretest-posttest scores statistically analyze used the t-test at 5% confidence level. The results showed that the collaboration skills of the experimental group and the control group were categorized as